ENT600 : Portable easy phototherapy / Norjah Othman … [et al.] - Othman, Norjah; Mohamed, Nor Marini; Musa, Lailatul Hazzliza; Muhamad, Maziran (2016)
The results from our observations, the percentage of baby jaundice tend to rise over the time. The number of beds was insufficient and the rate of infection also increasing. Therefore, we have decided to produce 'Portable Easy Phototherapy' to solve the problem. Phototherapy is an effective treatment to decrease bilirubin levels in infants with severe jaundice. It is widely used method of treating neonatal jaundice as it is far safer and it is easier to perform than exchange transfusion. The action of LED UV light has been shown to break down bilirubin thereby effectively reducing its concentration and preventing brain damage. It is generally accepted that light in the visible blue spectrum with wavelength 420 to 480 nanometer is of most therapeutic value and hence blue tube lights transparent filter or white tube light with blue filters are used in phototherapy units. It is believed that if the distance of 45cms between phototherapy source and neonatal kept then the wave length of 420 to 480 nanometer is achieved.